2017
DOI: 10.1051/matecconf/201710603013
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity of plasticized sulfur-extended asphalt: two-factor sequential optimization

Abstract: Abstract. The compounding properties of construction materials for pavements strongly depend on dynamic viscosity of the binder. The favorable class of binder is plasticized sulfur-extended asphalt. Unfortunately, the viscosity of such a binder has not been studied in detail. In the present work we have performed experimental two-factor sequential constrained optimization of the viscosity. The binders under examination were made of asphalt, sulfur and paraffin. It was revealed that the addition of sulfur and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In addition, in works [ 5 , 6 , 7 ] it is shown that the introduction of sulfur provides a decrease in the amount of bitumen in the asphalt concrete mixture, as well as a decrease in the temperature of preparation and laying The use of sulfur improves not only the operational properties of sulfur asphalt concrete (SEA) but also the technological properties of the mixture. Thus, in [ 8 ], the rheological properties of a bitumen-sulfur melt were investigated and it was shown that the introduction of sulfur significantly reduces the viscosity of such melts. Physicochemical processes of interaction of bitumen with sulfur are described in [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in works [ 5 , 6 , 7 ] it is shown that the introduction of sulfur provides a decrease in the amount of bitumen in the asphalt concrete mixture, as well as a decrease in the temperature of preparation and laying The use of sulfur improves not only the operational properties of sulfur asphalt concrete (SEA) but also the technological properties of the mixture. Thus, in [ 8 ], the rheological properties of a bitumen-sulfur melt were investigated and it was shown that the introduction of sulfur significantly reduces the viscosity of such melts. Physicochemical processes of interaction of bitumen with sulfur are described in [ 9 ].…”
Section: Introductionmentioning
confidence: 99%